Health-related quality of life and treatment satisfaction of patients with cardiovascular disease in Ethiopia - Tito, Kebron; Gebremariam, Girma Tekle; Beyene, Kebede; Sander, Beate; Gebretekle, Gebremedhin Beedemariam (Frontiers in Public Health, 2022)
Purpose Cardiovascular disease is the most prevalent health problem associated with poorer health-related quality of life (HRQoL). We aimed to assess HRQoL and treatment satisfaction of cardiovascular disease patients in Ethiopia. Methods A cross-sectional survey was conducted among adults attending the outpatient cardiac clinic at Tikur Anbessa Specialized Hospital from July to September 2021. Patients were recruited consecutively during follow-up visits. Treatment Satisfaction Questionnaire for Medication and European Quality of life questionnaires were used to evaluate treatment satisfaction and HRQoL, respectively. Kruskal-Wallis and Mann-Whitney U-tests were used to compare utility weights between patient subgroups. Utility values were computed using disutility weights of the Ethiopian general population derived using a hybrid regression model. Tobit regression modeling was used to explore factors associated with poor HRQoL. Statistical significance was determined at p < 0.05. Results A total of 357 patients participated in the study with a mean age of 49.3 ± 17.8 years. The most frequently reported health problems were pain/discomfort (75.4%), followed by mobility (73.4%). The median (interquartile range) European Quality questionnaires five dimensions with five levels utility (EQ-5D-5L) and European Quality of life Visual Analog Scale scores were 0.84 (0.55–0.92) and 70.0 (50.0–85.0), respectively. The highest and lowest mean (standard deviation) treatment satisfaction scores were for the convenience and safety satisfaction dimensions: 87.7 (17.9) and 53.1 (33.5), respectively. Unemployment, older age, previous hospital admission, non-adherence to lifestyle modification, and presence of three or more cardiovascular disease factors were significantly negatively associated with HRQoL. Conclusions Overall, the study found that cardiovascular disease had a profound negative effect on HRQoL and patient treatment satisfaction. We suggest that interventions to enhance HRQoL and treatment satisfactions should focus on modifiable associated factors including lifestyle changes and controlling disease progression.